Revitalisasi Wisata Otentik Berbasis Budaya: Pengalaman Imersif Mercer University USA di Desa Wisata Tajen - Indrayani, I Gusti Ayu Putu Wita; Adi, Ida Ayu Sri Puspa; Iswarini, Ni Ketut (Politeknik Piksi Ganesha Indonesia, 2025)
The existence of Balinese culture is essential in the development of tourism in Bali. However, many tourists only see cultural elements like janur (young coconut leaves) as aesthetics without understanding their philosophical meaning. In response, the Room Division Program of Bali Tourism Polytechnic conducted a community service program in Tajen Tourism Village, collaborating with Mercer University, USA, through the Custom Program Summer 2024. This program involved international students in an experiential learning activity to deepen their understanding of Balinese traditions. The initiative aimed to enhance cultural tourism experiences while supporting the sustainable development of the village.